Reexamining feedback on L2 digital writing - Elola, Idoia; Oskoz, Ana (Studies in Second Language Learning and Teaching, 2022)
The integration of digital multimodal composing (DMC) in the second language (L2) and heritage language (HL) classrooms has expanded our notion of writing, shifting from a focus on the written mode to include other modes of expression (e.g., visual, textual, or aural). Notwithstanding the increasing presence of L2 multimodal learning tasks, which combine different semiotic resources (e.g., language and visual components such as images or videos) as intrinsic elements used to generate meaning, instructors have not yet modified the way in which they provide feedback. That is, despite the increasing integration of different modes in a multimodal task, instructors still focus exclusively on language development – replicating the feedback behaviors modeled by non-digital writing assignments – rather than on all the components of multimodal texts. In digitally influenced environments and societies, however, there is a need to reconsider our approaches to feedback to pay greater attention to the linguistic and nonlinguistic elements of DMC. With the scarcity of research on feedback in DMC, this article first identifies a gap in multimodal teaching and research regarding the role and focus on feedback in DMC, and, second, provides an assessment rubric from which to base formative feedback that addresses both linguistic and nonlinguistic elements to help students develop their multimodal texts.